2000
DOI: 10.1089/10430340050016238
|View full text |Cite
|
Sign up to set email alerts
|

Dynein- and Microtubule-Mediated Translocation of Adenovirus Serotype 5 Occurs after Endosomal Lysis

Abstract: Modified viruses are used as gene transfer vectors because of their ability to transfer genetic material efficiently to the nucleus of a target cell. To better understand intracellular translocation of adenovirus serotype 5 (Ad), fluorophores were covalently conjugated to Ad capsids, and movement of fluorescent Ad within the cytoplasm was observed during the first hour of infection of a human lung epithelial carcinoma cell line (A549). Ad translocation was characterized with respect to its ability to achieve n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
211
1
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 218 publications
(219 citation statements)
references
References 97 publications
5
211
1
2
Order By: Relevance
“…[22][23][24][25][26] In these studies, significant accumulation of viral particles near the nucleus was seen within 1-2 h. The actin network can also act as a transport conduit, as demonstrated by bacculovirus, which uses the actin network exclusively for transport, 27 and HIV, which uses both actin and microtubule networks for cytoplasmic trafficking. 22 Nonviral vectors, depending on their mode of transfection, can also use cytoskeletal machinery to travel toward the nucleus.…”
Section: The Percent Of Apoptotic Cells (7sd) Is Shownmentioning
confidence: 79%
“…[22][23][24][25][26] In these studies, significant accumulation of viral particles near the nucleus was seen within 1-2 h. The actin network can also act as a transport conduit, as demonstrated by bacculovirus, which uses the actin network exclusively for transport, 27 and HIV, which uses both actin and microtubule networks for cytoplasmic trafficking. 22 Nonviral vectors, depending on their mode of transfection, can also use cytoskeletal machinery to travel toward the nucleus.…”
Section: The Percent Of Apoptotic Cells (7sd) Is Shownmentioning
confidence: 79%
“…Ad capsid proteins are known to interact with MTs and cytoplasmic dynein during transit to the nucleus. 40,41 We have previously shown that inhibition of cytoplasmic dynein activity in lacrimal acini severely impairs the formation of rab3D-enriched secretory vesicles. 27 However, direct dynein inhibition also prevents the recruitment of VAMP2-enriched secretory transport vesicles to the apical membrane in response to CCH, while this response is unaffected by Ad (data not shown), suggesting that some dynein-mediated traffic to the apical membrane can proceed normally in Ad-treated acini.…”
Section: Discussionmentioning
confidence: 99%
“…[72][73][74][75][76][77][78] Receptor binding leads to internalization of the virus by the cell through receptormediated endocytosis, lysis of the endosomal membrane, escape to the cytosol, trafficking along microtubules towards the nucleus, binding the nuclear envelope, and insertion of the viral genome into the nucleus. [79][80][81][82][83][84][85][86][87][88] The adenoviral reproductive cycle is a highly orchestrated process, and gene modification strategies, which enable selectivity, often reduce replication capacity. At the molecular level, completion of the infectious cycle relies on timely expression of a set of viral regulatory proteins that interact with essential endogenous cellular pathways that determine cell viability.…”
Section: Onyx 015mentioning
confidence: 99%